Hormonal Regulation and Physiological Adjustments of Wheat and Pea Plants Under Simulated Lunar Soil Conditions - Zuniga-Navarro, G (John Wiley and Sons Inc, 2025)
This study investigates the physiological and morphological responses of wheat (Triticum aestivum) and pea (Pisum sativum) grown in a mixture of lunar soil (LS) simulant and organic soil (OS). The experiment compared the growth of both pea and wheat in 100% organic soil (OS) and a 3:2 mixture of OS and LS (OS: LS). Wheat exhibited increased branching and root growth in OS: LS, while pea plants showed enhanced aerial elongation and altered branch morphology. Photochemical efficiency (Fv/Fm) and pigment concentrations were significantly affected, with both pea and wheat showing reduced chlorophyll content in OS: LS. Oxidative stress indicators, such as lipid peroxidation, exhibited higher levels in pea plants than wheat plants, particularly in the OS: LS mixture. Hormonal analysis performed by LC–MS/MS indicated significant increases in abscisic acid (ABA) and its catabolites in both pea and wheat in OS: LS, suggesting an adaptive response to suboptimal conditions. The results highlight species-specific growth strategies, with wheat investing more in root development and pea plants promoting aerial growth. These findings provide important insights into how essential crops could adapt to extraterrestrial soils, contributing to the development of sustainable agricultural practices for space exploration. Future research should focus on optimising crop performance based on species-specific adaptative responses in mixed-soil environments. © 2025 Scandinavian Plant Physiology Society.